Optical and Thermal Investigations of New Schiff Base/Ester Systems in Pure and Mixed States - Altowyan, Abeer S. (Polymers (Basel), 2021)
New mesomorphic series, 4-hexadecyloxy phenyl-imino-4′-(3-methoxyphenyl)-4″-alkoxybenzoates (An), were prepared and investigated with different thermal and mesomorphic techniques. The synthesized homologous series constitutes four members that differ from each other in the terminal length of flexible chain (n) attached to phenyl ester moiety, which varies between n = 6, 8, 10, and 12 carbons. A lateral CH(3)O group is attached to the central benzene ring in the meta position with respect to the ester moiety. Molecular structures of all newly prepared homologues were elucidated via FT-IR, (1)H and (13)C NMR spectroscopy. Mesomorphic and thermal properties were examined by differential scanning calorimetry (DSC), thermogravimetric analysis (TGA) and the mesophases identified by polarized optical microscopy (POM). DSC and POM examinations revealed that all members of the present series (An) exhibit a purely enantiotropic nematic (N) phase. Comparative evaluations and binary phase diagrams were established between the present homologues and their corresponding shorter one (Bn). The examination revealed that, the length of the flexible alkoxy chain incorporated into the phenylimino moiety is highly effective on the temperature range and stability of the mesophase observed. With respect to the binary mixtures An/Bn, the exhibited N phase showed to cover the whole composition range with eutectic behavior.